Certification of Uranium Isotope Amount Ratios in a Suite of Uranium Ore Concentrate Certified Reference Materials. Issue 1 (20th December 2021) - Zhang, Ruoxi; Nadeau, Kenny; Gautier, Eduardo Amilcar; Babay, Paola Alejandra; Ramella, José Luis; Virgolici, Marian; Serban, Andreea Elena; Fugaru, Viorel; Kimura, Yoshiki; Venchiarutti, Célia; Richter, Stephan; Aregbe, Yetunde; et al.
Abstract : In this study, data from thirteen laboratories from around the world are presented for a successful certification of uranium isotope ratios in uranium ore concentrate (UOC) certified reference materials from the National Research Council Canada. Different mass spectrometric measurement principles (including SF‐ICP‐MS, quadruple ICP‐MS, TIMS, MC‐ICP‐MS, SIMS and AMS) and measurement procedures were employed. In general, data from all sources exhibit good consistency with TIMS and MC‐ICP‐MS showing superior performance. The three candidate UOC CRMs (UCLO‐1, UCHI‐1 and UPER‐1) have natural uranium isotope ratios with certified values of 0.5304(7) × 10 −4, 0.5475(2) × 10 −4 and 0.5361(4) × 10 −4 for n ( 234 U)/ n ( 238 U) and 0.007 2563(13), 0.007 2563(10) and 0.007 2542(11) for n ( 235 U)/ n ( 238 U), respectively, with expanded uncertainty ( k = 2) applicable to the last digit of the value given in the parentheses. Information values for n ( 236 U)/ n ( 238 U) in these three CRMs, measured by AMS, are also provided: 10 × 10 −12, 200 × 10 −12 and 22 × 10 −12 . The uncertainties of the proposed certified values of uranium isotope ratios in UOC CRMs are superior to available reference materials, and the values of n ( 234 U)/ n ( 238 U) and n ( 236 U)/ n ( 238 U) show significant variation among the three CRMs. Abstract : Key Points Collaboration involving 13 international laboratories employing different mass spectrometric measurement principles (SF‐ICP‐MS, Q‐ICP‐MS, TIMS, MC‐ICP‐MS, SIMS, AMS) and measurement procedures. Successful certification of uranium isotope ratios in uranium ore concentrate CRMs UCHI‐1, UCLO‐1 and UPER‐1 from the National Research Council Canada. Suitable for validation of methods used for uranium isotope ratio measurements.